New Common Fixed Points for Total Asymptotically Nonexpansive Mapping in CAT(0) Space (Baghdad Science Journal, 2021)
Strong and ∆-convergence for a two-step iteration process utilizing asymptotically nonexpansive and total asymptotically nonexpansive noneslf mappings in the CAT(0) spaces have been studied. As well, several strong convergence theorems under semi-compact and condition (M) have been proved. Our results improve and extend numerous familiar results from the existing literature.